Mammary Fibroepithelial Hyperplasia in a Male Cat - Bonatto, Giovanna Lapkoski; e Silva, Victoria Gariba; Favero, Lucas Jocemir; Kano, Natália Noreika; de Sousa, Renato Silva; Albernaz, Vinicius Gonzalez Peres (Acta Scientiae Veterinariae, 2021)
Background: Feline mammary hyperplasia (FMH) is a benign disease that commonly affects young females, once it is caused by the exaggerated stimulation of endogenous or exogenous progestogen. FMH leads to acute edema and inflammation of the mammary glands and frequently evolve to ulcerations, secondary infections, and systemic clinical signs. Even though it is rare in male cats, progesterone therapy or an unknown endogenous source of hormone can cause the disease. This report aims to describe a case of FMH in a male feline with no history of hormonal treatment and treated with radical surgical resection. Case: A 7-month-old intact male domestic shorthair cat was presented due to acute onset of generalized mammary tumors which had progressed for 18 days. Tumors size had 5 cm large in diameter, symmetric, bilateral, and affected all mammary glands. The tissue was firm, hyperemic, and ulcerated. FMH was initially suspected but with a differential diagnosis for mammary adenocarcinoma. Except for pain on tumor palpation, there was no other clinical abnormality. Survey thoracic radiographs and abdominal ultrasound did not find signs of metastasis or hermaphroditism. Fine-needle aspirate biopsy and further cytological examination were inconclusive. Surgical resection through a single-stage bilateral total mastectomy and reconstruction using a left flank fold flap was elected. There were no intraoperative complications and the cat recovered well, with good healing and no clinical signs 21 days after the surgery. Histological examination of the mammary glands confirmed the diagnosis of FMH due to the non-neoplastic characteristics and tissue’s benign biological behavior. Eleven months after diagnosis, the cat was asymptomatic. Discussion: The FMH frequently affects young females and is associated with gestational periods, the end of the estrous cycle, and, most commonly, hormonal therapy with synthetic progesterone. Male cats are rarely affected with or without a history of progesterone administration, which is commonly used for treatment of dermatopathies, urinary incontinence, control of behavioral changes, or mistakenly as a contraceptive. Clinical signs are the acute onset of mammary tumors with firm consistency, inflammation, ulcerated areas, absence of mammary secretion, and mobility difficulty due to local swelling. Systemic clinical signs including apathy, anorexia, fever, and dehydration can occur. The main differential diagnosis is mammary neoplasia and diagnosis is suspected by the patient’s history, disease progression, and histological examination. Conservative treatment using a progesterone inhibitor, such as aglepristone, can be performed but usually take a few weeks to promote total remission, may require additional administration, and does not prevent a possible recurrence. Radical mastectomy is an alternative to late-stage disease. It was chosen toperform a single-stage bilateral mastectomy for surgical removal of the FMH in this case mainly considering that it was a male cat with no detectable progesterone source, marked swelling, and a clinical condition that could deteriorate quickly. The FMH prognosis is good when there are no secondary infections or systemic signs, making it possible to maintain quality of life after treatment. The FMH must be considered a differential diagnosis for feline mammary tumors, regardless of gender and history of progesterone administration.